Upaya Meningkatkan Keterampilan Proses Sains Melalui Penerapan Model Pembelajaran (Experiental Learning) Pada Siswa Kelas III SDN 001 Bangkinang Kota - Iqbal; Putri Hana Pebriana; Astuti (Jurnal Dharma PGSD, 2022)
This research was motivated by the low science process skills of students in class III thematic learning at SDN 001 Bangkinang Kota. This study aims to improve students' process skills by using the Experiential Learning model in class III learning at SDN 001 Bangkinang Kota. This type of research is classroom action research (CAR). This research was carried out in 2 cycles and each cycle was carried out in two meetings. The subjects of this study were the third grade students of SDN 001 Bangkinang Kota, totaling 17 students with 9 male students and 8 female students. Data collection techniques used in this research are observation and documentation techniques. Based on the results of the study, it can be concluded that in the first cycle it was still quite adequate with an average of 74.11%, then from 17 students only 12 students or 70.58% achieved individual mastery. Student learning outcomes in cycle II were classified as good with an average of 80.00% and 14 students completed or 82.35% who achieved individual mastery. Thus, it can be concluded that the application of the Experiential Learning model can improve the skills of the learning process of living things in third grade students of SDN 001 Bangkinang Kota.